Watershed-presegmented snake for boundary detection and tracking of left ventricle in echocardiographic images - Krishnan, Shankar M. (2009)
In this paper,an automated method of boundary detection of the left ventricle (LV) is proposed. The method uses a watershed transform and morphological operation to locate the region containing the LV,then performs snake deformation with a multiscale directional edge map for the